Unraveling late Quaternary atmospheric circulation in the Southern Hemisphere through the provenance of Pampean loess - Torre, Gabriela; Gaiero, Diego Marcelo; Coppo, Renata; Cosentino, Nicolas Juan; Goldstein, Lawrence S. B.; de Vleeschouwer, Francois; Le Roux, Gael; Bolge, Louise; Kiro, Yael; Oliveira Sawakuchi, André (Earth-Science Reviews)
The Pampean loess is the most extensive continental paleo-record of aeolian material in the Southern Hemisphere, recording the deposition of dust transported by two major zonal wind systems: the southern westerly winds and the subtropical jets. In order to increase the understanding on paleo-atmospheric circulation over the Southern Hemisphere, we evaluate dust provenance through REE, Nd, Sr and Pb isotopes in three sections deposited during late Pleistocene-early Holocene across 700 km in the loess belt of the Pampean region in central Argentina. The isotopic comparison of loess from the three sections with southern South American (SSA) potential dust sources show that (1) sources from the southern Altiplano to latitudes of northern Patagonia supplied dust to the Pampas, (2) the slight Sr[sbnd]Nd isotopic difference between fine and coarse loess may be attributable to grain size effects rather than to differences in provenance, and (3) higher mass accumulation rates in the Pampas are associated with an increased presence of dust originated in the southern Altiplano and southern Puna during the spans of 43–41 ka BP, 20–18 ka BP, 14.6–12.6 ka BP and 11.4–8.9 ka BP. We associate these rises in continental dust fluxes with climatic transitions from wetter to drier periods in the Puna-Altiplano Plateau related to synchronous climatic shifts to humid conditions at the Pampean Plain, probably triggered by El Niño-like conditions. The isotopic comparison with modern SSA dust indicates similar provenance compared to paleo-dust records, suggesting almost constant dust sources from MIS 3 to modern times and/or modest changes in the geochemical signature under the activation/deactivation of the different dust sources. Moreover, contrasting the isotopic signature of the loess sections with more distal palaeoarchives (i.e., South Atlantic Ocean marine sediment cores and Antarctic ice cores), the new data suggest that contrary to previous ideas, the Pampean Loess was not an important source of dust to these regions. Also, a ...